The Impact of Tourism Sector on Economic Growth in OIC Countries - Qoir, Nurlaila Madinatul (SMART Insight, 2023)
This study aims to analyze the effect of economic growth in 8 OIC countries, namely Malaysia, Turkey, Indonesia, Bangadesh, Egypt, Iran, Nigeria, Pakistan and also see the development of halal tourism in OIC countries. This study uses a mix method, namely the analysis of panel data regression methods with 8 country objects which are members of the OIC countries within a period of 10 years starting in 2010 to 2019. To find out the development of halal tourism, this research uses descriptive qualitative methods by collecting and summarizing research journals on the development of halal tourism that have existed before. The results of the study show that the number of tourists has a positive influence on economic growth in 8 OIC countries. For the development of halal tourism, several OIC countries have made innovations and updates for the growth of the halal tourism sector, such as providing Muslim-friendly facilities at each airport, sharia-based hotels, providing halal food, drinks in restaurants, and places of worship for Muslim tourists. In addition, some countries have also begun to carry out attractive promotions for the halal tourism sector so as to attract Muslim tourists to visit the country.